Incidence and Mortality of Cardiovascular Disease in the Republic of Kazakhstan: 2004-2017 - Gulbarshyn Mukasheva; Madina Abenova; Askhat Shaltynov; Oxana Tsigengage; Zhanna Mussabekova; Tolkyn Bulegenov; Gulnara Shalgumbaeva; Yuliya Semenova (Tehran University of Medical Sciences, 2022)
Background: We aimed to evaluate the impact of national health programs implemented in Kazakhstan from 2011 on CVD incidence and mortality. Methods: Incidence and mortality rates from CVD were studied in Kazakhstan from 2004 to 2017. The official data obtained from "Medinform" company were analyzed based on the annual population statistics. Results: There was an increase in the incidence of cardiovascular disease among the population of Kazakhstan from 1845.4 per 100,000 in 2004 to 2597.5 per 100,000 in 2017. This might be attributed to the implementation of the national health programs, which improved early CVD identification. Incidence of ischemic heart disease (IHD) was grown almost in all provinces of Kazakhstan during the study period. The mortality from cardiovascular disease had a considerable decline over the study period, in particular after 2010, it might be influenced by early diagnosis and provision of timely treatment. Conclusion: The experience of Kazakhstan national health programs shows improved identification of CVD and IHD and timely treatment for cardiovascular disease. A significant variation in incidence and mortality rates of cardiovascular disease was observed between the country provinces.